Rooting binder-free tin nanoarrays into copper substrate via tin-copper alloying for robust energy storage - Jiangfeng Ni (Nature Portfolio, 2020)
The authors here report a binder-free electrode based on tin nanoarrays deposited on copper substrate. It is found that the locally formed electrochemically inactive tin-copper alloys work as a glue that bridges tin and copper to survive harsh cycling conditions in sodium ion batteries.